Tinggalan Arkeologis di Pesisir Selatan Pulau Rupat, Indikasi Hunian Pada Lahan Basah - Nenggih Susilowati (Berkala Arkeologi Sangkhakala, 2008)
AbstractThe selection of a settlement area was decided by many factors which have as a background of the society. The coastal was potential to be a settlement area. The south of Rupat coastal with its archaeological remains described that there was a settlement area in there.